An exploratory of conceptual model of poverty information crowdsourcing for zakat distribution / Ummu Fatihah Mohd Bahrin - Mohd Bahrin, Ummu Fatihah (2015)
This study attempts to examine the current situation of identifying asnaf for zakat disbursement towards the proposed poverty information crowdsourcing for zakat distribution. In a way, zakat is seen a tool to reduce poverty. The information about the asnaf is available, but the society does not know where to channel the asnaf information. If the process of getting asnaf information is slow, therefore the zakat aid is not being able to give at the right time, perhaps not to the rightful asnaf as well. The objectives of this study are to identify the current practise of reporting poverty in Selangor; to identify the issues and challenges of identifying asnaf for zakat distribution; and to construct a conceptual model of poverty information crowdsourcing for zakat redistribution. Crowdsourcing is seen as a technique which it helps the zakat institution to get the information very quickly. The method used is an interpretive qualitative methods and data collection tools used is interviews and document review. Purposive sampling methods applied with the sample size of four. Respondents or multi-stakeholders are coming from different background in society to share experience on identifying asnaf. As a result, there are several factors, both internal and external factors identified as issues & challenges of identifying asnaf. This research also provides a conceptual model of poverty information crowdsourcing which later can be utilized in identifying asnaf. The future work can be enhance with the larger sample, the bigger scope and the covered the whole process of distribution of zakat.